the simplest form of 5x + 3y +2x - 6y is 7x-3y
4x + 3y - 2x - 7y2x - 4y
3x + 7y
6x plus 4y
5x+2x-3y+y = (5+2)x+(-3+1)y = 7x - 2y
6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y
4(2x + 3y)(2x + 3y)
2x + 4y - 5x + 3y = 7y - 3x
2x plus 3y
2x+3y=40-2x+2y=20Since 2x does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 2x from both sides.3y=-2xDivide each term in the equation by 3.(3y)/(3)=-(2x)/(3)Simplify the left-hand side of the equation by canceling the common terms.y=-(2x)/(3)if you were solving for x It would be x=-(3y)/2
2x + 3y + 4x + 9y = 2x + 4x + 3y + 9y = 6x + 12y which can be simplified to 6(x + 2y)
Yes. -4x is one, and 3y is one. They are combined with a "+" sign, and together they are a polynomial.
Collect like terms: 2x + 3y + 3y - 5 - 6 2x + 6y - 11
-2x plus 3y equals 1
It's just a mathematical polynomial: 7x + 3y.
6x plus 3y minus 2x plus 5y equals 4x plus 8y.
10x - 3y + 2x - 4y =(10x + 2x) + (-3y - 4y) =12x - 7y
2x2 + 6xy = 2x (x + 3y)
2x + 3y - x + 5y combine the like terms 2x - x + 3y +5y simple arithmetic x + 8y
Answer = -2x + 3y - 6 Are you sure you asked the question correctly?
2x plus 3y is not an equation, it is an expression.
2x + 3y = 1 y = 1/3 - 2x/3
See definition of polynomial and monomials. You will see.